Analysis of environmental risk factors that affect the oil palm production / Nor Hayati Fauzi - Fauzi, Nor Hayati (Faculty of Plantation and Agrotechnology, 2016)
Environmental risk factor is one of the most important factor that can affect oil palm production or yield. This study focus to the rainfall intensity, rainfall duration, temperature and relative humidity as the environmental factors which can affect the oil palm yield. Environment is an uncontrolled situation that can be the problems to the planters in handling their crop. Environmental factor provided by nature affect the oil palm production when input requirement for oil palm growth was below or over the optimum rate (rainfall intensity, rainfall duration, temperature and relative humidity). The aims of this study is to identify the environment risk factor due to the low productivity among the smallholder. The data was obtained through questionnaire that was distributed by random sampling technique to the smallholder (FELCRA Sri Mendapat, Melaka). The result shows that rainfall intensity, rainfall duration and temperature have an effect to the productivity of the smallholder, while relative humidity has no effect to the oil palm production.